Análisis del Proceso de partición de bienes sucesorios No. 1120220130100 dado en la Unidad Judicial Multicompetente Civil con sede en el Cantón Catamayo, Provincia de Loja - Paccha Castillo, Paola de los Ángeles (2024)
The present thesis focuses on the analysis of the partition of estate assets process No. 11202-2013-0100, carried out in the Unidad Judicial Multicompetente Civil located in the Catamayo Canton, Loja Province. The main objective is to examine the role of evidence in this judicial process, as well as its impact on the final distribution of hereditary assets. The research is based on a solid theoretical framework that encompasses the historical evolution of evidence and its application in the Ecuadorian legal context. Different types of evidence are explored, such as documentary, testimonial, and expert evidence, emphasizing the importance of rigorous and objective assessment by the judge. Furthermore, comparative legislation on succession and asset partition in Colombia, Argentina, and Peru is analyzed to identify best practices and potential solutions to the challenges faced by the Ecuadorian system. The analysis of case No. 11202-2013-0100 reveals the complexity of the partition of estate assets processes and the importance of having solid and complete evidence to support the claims of the heirs. The research highlights the influence of evidence on judicial decisions and the final distribution of assets, as well as the fundamental role of substantive norms and jurisprudence in resolving such disputes. In conclusion, this thesis contributes to the understanding of the partition of estate assets process in Ecuador and offers recommendations to strengthen the justice system in this area. The research underscores the need for rigorous and objective evaluation of evidence, the importance of proper application of substantive norms, and the utility of comparative law to improve the efficiency and effectiveness of the Ecuadorian system.